ChemInform Abstract: 1, 3‐Dicyclohexylimidazol‐2‐ylidene as a Superior Ligand for the Nickel‐Catalyzed Cross‐Couplings of Aryl and Benzyl Methyl Ethers with Organoboron Reagents. Issue 17 (April 2015) - Tobisu, Mamoru; Yasutome, Ayaka; Kinuta, Hirotaka; Nakamura, Keisuke; Chatani, Naoto
Abstract The developed reaction system is inapplicable to secondary benzylic ethers other than 2‐[methoxy(phenyl)methyl]naphthalene (IX).